1991
DOI: 10.1002/jmv.1890350416
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the immunogenicity of yeast‐derived (recombinant) and plasma‐derived hepatitis B vaccine in infants

Abstract: The immunogenicity of plasma-derived (HB Vax,MSD) and recombinant hepatitis B virus (Engerix B, SK&F) vaccines was evaluated in infants born to hepatitis B virus carrier mothers. The vaccination was carried out at 1 day, 1 month, and 6 months of age using 10 micrograms of the vaccine given intramuscularly. A total of 83/88 (94.3%) and 74/79 (93.6%) of the infants receiving the plasma-derived vaccine and yeast-derived vaccine showed antibody to hepatitis B surface antigen (anti-HBs). None of the maternal factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…HBeAg positivity rate among HBsAg positive antenatal women have been shown to vary widely in different geographical regions around the world [22,[24][25][26][27][28][29][30][31][32][33]. HBeAg positivity in our study (57%) was similar to that previously reported in a study by Biswas [23].…”
Section: Discussionsupporting
confidence: 93%
“…HBeAg positivity rate among HBsAg positive antenatal women have been shown to vary widely in different geographical regions around the world [22,[24][25][26][27][28][29][30][31][32][33]. HBeAg positivity in our study (57%) was similar to that previously reported in a study by Biswas [23].…”
Section: Discussionsupporting
confidence: 93%
“…Preterm delivery is a common maternal complication of hepatits in pregnancy and is observed in the following studies with rates: Caesarean section rate in our study is 33.5% which is comparable to that done by Suruchi Shukla 16 , where it was 29.7%. Maternal complications rate encountered in present study is nearly similar to that seen in general population Studies 6.3% Sunita Mittal et al, 5 6.3% Gill et al, 6 5% Ahmad et al, 7 12.8% Biswas et al, 8 2.3% Panda et al, 9 2.6% Sehgal et al 10 , 2.6% Mean age in years Sabria Rashid et al 12 28.5 years. Suruchi Shukla et al 13 23.85 years Present study 23.61 years Percentage of subjects in 3 rd trimester Jaisiwal et al 14 72% Patra et al 15 72% Suruchi Shukla et al 16 75% Present Study 50.4% Preterm labour percentage Suruchi Shukla et al 16 17% Medhat et al .…”
Section: Discussionsupporting
confidence: 82%
“…However, the anti-HBs GMT of the PDHBV was higher (P<.05) than that elicited by RYHBV. Panda et al 32 evaluated immunogenicity of PDHBV and RYHBV in infants born to hepatitis B virus carrier mothers. The RYHBV gives marginally lower antibody titre than the PDHBV.…”
Section: Discussionmentioning
confidence: 99%